Recursive structures and finite impulse response implementations of linear multiuser detectors for an asynchronous CDMA system. - Uppala, S.V (IEEE Journal on selected areas in communications)
We present order-recursive structures for implementing the linear decorrelating and linear minimum mean square error (MMSE) detectors in a computationally efficient manner. These infinite memory length, linear time invariant, noncausal systems can be approximated by implementing them as K-input K-output finite impulse response (FIR) filters. We developed a linear multiuser receiver architecture called a recursive linear multiuser detector which has lower computational and memory requirements then an equivalent tap delay line FIR filter implementation. We establish the tradeoff between window length and bit error rate and find that relatively small window size yields performance indistinguishable from the ideal decorrelating detector and the ideal MMSE detector